ҚАДРИЯТЛАРНИ ҚАДРЛАШ-ГУМАНИСТИК ВАЗИФАМИЗДИР - Таспанова, Ж. (SCIENCE and SOCIETY, 2018)
The article presents the ideas and thoughts values, about the cause-and consecutive-events and devotion, to material and spiritual values.
Keywords: қадриятлар; аксиологик тарбия; энг муҳим илмий-маърифий вазифалар